Pengaruh Manajemen Rantai Pasokan Hijau, Pemasaran Hijau, dan Inovasi Hijau terhadap Kinerja Keuangan Perusahaan - Jonathan Reinhard Mangapul; Rakendro Wijayanto (Jurnal Kendali Akuntansi, 2026)
This study aims to analyze the effect of Green Supply Chain Management, Green Innovation, and Green Marketing on corporate financial performance. This research applies a quantitative approach with a causal associative research design. The population of this study consists of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research sample was selected using a purposive sampling method based on predetermined criteria. The data used in this study are secondary data obtained from annual reports and sustainability reports. Financial performance is measured using Tobin’s Q, while Green Supply Chain Management, Green Innovation, and Green Marketing are measured using the content analysis method. The data analysis technique used is multiple linear regression analysis. The results indicate that Green Supply Chain Management and Green Innovation have a positive effect on corporate financial performance. Meanwhile, Green Marketing has a negative effect on corporate financial performance. These findings suggest that implementing green strategies through supply chain efficiency and sustainable innovation can improve firm value, while green marketing strategies need to be managed effectively to provide optimal financial benefits.